Laughed 'til he died : a death on demand mystery - Hart, Carolyn G. (Hart, Carolyn G. Death on demand series., 2010)
Three deaths are linked to Broward's Rock Island's youth recreation center, and its director. When she asks Max to help clear her name, Annie is right there with her husband to help.